ENTANGLED LEGAL PLURALISM: AN INCLUSIVE MODEL FOR RESOLVING INDIGENOUS NATURAL-RESOURCE DISPUTES BASED ON THE SDGS AND SOCIAL JUSTICE - Johanis Polii; Nopesius Bawembang; Joni Kutu' Kampilong; Chrestotes Lang; Melissa Suoth (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study focuses on the effect of entangled legal systems on the administration of natural resources in multi-ethnic communities in North Sulawesi. We raised three fundamental issues: (1) the mix of formal laws and customary practices as hybrid-norm zones as communities renegotiate the social boundaries and move between different governance forums; (2) formal and informal, gauging the process of renegotiation of the boundaries within communities; and (3) safeguards within communities that promote or impede inclusive participation in dispute resolution. Using a multi-method design consisting of participatory mapping, document review, panel observations, focus group discussions, and expert network analysis, three different hybrid-norm zones were identified (shared-use agroforestry in Minahasa, rotational fishing quota in Sangihe, and sacred resource reserves in Talaud). Seasonal redraw rate data (78%, 65%, 72%) along with average forum shifts (2.3, 1.9, 2.1) indicate that there is a strong correlation between the intensity of boundary-making and the procedures of recursion. Documentary analysis revealed evidence of negotiated joint authorsship in the form of signatures from customary and state actors for documents for which joint authorship is indicated in one-third of the dispute records. Finally, expert accessibility skews and secures the take-up of experts, underscoring the constant equity holes. We conclude that inclusive pluralism results from the mechanisms of spatial, procedural, and documentary reinforcement of each other in a permanent feedback loop. We recommend that hybrid rules be made law, platforms that engage a large number of people be increased, and digital tools be applied to flexible and fair governance.